2018
DOI: 10.1029/2017jd027970
|View full text |Cite
|
Sign up to set email alerts
|

The Excitation of Secondary Gravity Waves From Local Body Forces: Theory and Observation

Abstract: We examine the characteristics of secondary gravity waves (GWs) excited by a localized (in space) and intermittent (in time) body force in the atmosphere. This force is a horizontal acceleration of the background flow created when primary GWs dissipate and deposit their momentum on spatial and temporal scales of the wave packet. A broad spectrum of secondary GWs is excited with horizontal scales much larger than that of the primary GW. The polarization relations cause the temperature spectrum of the secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
180
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(190 citation statements)
references
References 50 publications
(94 reference statements)
9
180
1
Order By: Relevance
“…This results in time‐dependent, spatially and temporally localized horizontal accelerations of the background flow (i.e., local body forces) in the direction the MWs were propagating (in the intrinsic reference frame) before breaking. These local body forces cause the background flow to become unbalanced, which results in the creation of counterrotating mean wind cells and the generation of secondary GWs (Vadas et al, , ). These secondary GWs are created with concentric ring structure, propagate upward and downward away from the body force, have their largest amplitudes in and against the force direction, and propagate in all azimuths except those perpendicular to the force direction.…”
Section: Response Of the Atmosphere To Strong Mw Events During The Wimentioning
confidence: 99%
See 3 more Smart Citations
“…This results in time‐dependent, spatially and temporally localized horizontal accelerations of the background flow (i.e., local body forces) in the direction the MWs were propagating (in the intrinsic reference frame) before breaking. These local body forces cause the background flow to become unbalanced, which results in the creation of counterrotating mean wind cells and the generation of secondary GWs (Vadas et al, , ). These secondary GWs are created with concentric ring structure, propagate upward and downward away from the body force, have their largest amplitudes in and against the force direction, and propagate in all azimuths except those perpendicular to the force direction.…”
Section: Response Of the Atmosphere To Strong Mw Events During The Wimentioning
confidence: 99%
“…Vadas et al () calculated the theoretical spectra of secondary GWs from MW breaking during the winter over McMurdo. They found that these spectra are quite broad and have λ H ∼500 to thousands of kilometers, λ z ∼10–150 km, and c H ∼50–250 m/s.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gravity waves in the upper atmosphere can still be primary waves (Vadas & Fritts, ; Vadas, ). In addition, there is evidence that gravity waves observed in the upper mesosphere and in the thermosphere are also generated from the body forces that result from the dissipation of the primary gravity waves (Vadas, ; Vadas et al, , ). These gravity waves have large scales and high horizontal phase speeds; they can induce traveling ionospheric disturbances (Francis, ; Richmond, ; Vadas & Nicolls, ; Vlasov et al, ).…”
Section: Introductionmentioning
confidence: 99%